SMEs Assistance and Technology Transfer "Nata Gel" in the Saung Taleus Group - Ardiani, Septia; Rahmayanti, Handika Dany; Akmalia, Nurul; Mulyana, Raina; Ikhwannanda, Dias (Jurnal Pengabdian Masyarakat Progresif Humanis Brainstorming, 2023)
Saung Taleus is an SMEs group that produces food made from taro, its members are located in Bogor and its surroundings. The products produced are mostly packaged food products, including taro flour, taro chips, taro cake, taro cheese sticks, taro brownies, and others. The shelf life of these products is not long, so technology is needed to extend their shelf life. Assistance was provided to SMEs and the transfer of "Nata Gel" technology to the Saung Taleus Group to help extend the shelf life of its products. The team handed over 1000 packs of "Nata Gel" to Saung Taleus partners to be applied to their respective products. From the questionnaire, it was found that the satisfaction level of participants in mentoring SMEs and technology transfer reached 85%. This shows that this activity was very successful.